Uterine smooth muscle tumor of uncertain malignant potential: a case diagnosis, management and follow-up in the department of gynecology-obstetrics II of the Hassan II teaching hospital of Fes in Morocco - Conte, Alpha Boubacar; Jamor, Jihad; Alaoui, Fatima Zohra Fdili; Jayi, Sofia; Chaara, Hikmat; Melhouf, Moulay Abdelilah (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Rarely diagnosed in authors department, uterine smooth muscle tumor of uncertain malignant potential (STUMP) is one of the histologic types of uterine sarcoma. Among women undergoing hysterectomy or myomectomy for a presumed diagnosis of leiomyoma, 0.01% receive a diagnosis of STUMP. Authors report a case occurring to a patient aged of 55 which was diagnosed, managed successfully and followed-up in authors department.